Flypaper effects of Central Transfers on the spending behaviour of Ghana’s central region local governments: Does status matter? - Christopher Dick-Sagoe; Ernest Ngeh Tingum; Peter Asare-Nuamah (Masyarakat, Kebudayaan dan Politik, 2022)
Fiscal system incentivises local government officials to depend on central government’s transfers to fund their budgets. This paper examines whether district and municipal status local government officials exhibit the same spending behaviour when presented with central government’s transfers. The paper uses the panel data model to estimate the flypaper effect on district and municipal status local governments in the Central Region of Ghana from 2008 to 2015. The result shows differences in spending behaviour between district and municipal status local governments, where the flypaper effect is more pronounced on municipal status local governments (52.6%) than district status local governments (44.8%). Though municipal local governments are financially better in raising own-source revenues compared to the district local governments, the design of the fiscal system tends to make municipal local governments more reliant on central transfers than on expenditure of own-source revenues. This reduces interest in raising own-source revenue and its expenditure, a situation which has an adverse long-term impact on decentralisation in terms of citizen empowerment and participation. The study recommends an optimal level of central transfers which will serve the purpose of correcting vertical and horizontal imbalances, as in theory, and at the same time promote the ideals of decentralisation (citizen empowerment and participation).